Measurement of the inclusive isolated prompt photons cross section in pp collisions at s√=7 TeV with the ATLAS detector using 4.6 fb−1 - Onofre, A. (2014)
A measurement of the cross section for the production of isolated prompt photons in pp collisions at a center-of-mass energy s√=7  TeV is presented. The results are based on an integrated luminosity of 4.6  fb−1 collected with the ATLAS detector at the LHC. The cross section is measured as a function of photon pseudorapidity ηγ and transverse energy EγT in the kinematic range 100≤EγT<1000  GeV and in the regions |ηγ|<1.37 and 1.52≤|ηγ|<2.37. The results are compared to leading-order parton-shower Monte Carlo models and next-to-leading-order perturbative QCD calculations. Next-to-leading-order perturbative QCD calculations agree well with the measured cross sections as a function of EγT and ηγ.